New absolute paleomagnetic intensity data from Cenozoic basalts of Northeast China and exploring rock-magnetic parameters for efficient sample preselection on the Tsunakawa–Shaw paleointensity method - Hyeon-Seon Ahn; Youn Soo Lee; Yuhji Yamamoto (Earth, Planets and Space, 2024)
Abstract Despite being essential in determining absolute paleomagnetic field intensity (API) with high fidelity over Earth science research topics, API determination still suffers little quantitative success. This is due to common nonideal magnetic behaviors in experiments using natural rocks caused by physiochemical changes in the magnetic minerals contained. Although linking rock-magnetic parameters to API results may be fundamental, negligible effort has been made using the Tsunakawa–Shaw (TS) API method despite its potentially high experimental success rate in overcoming nonideal magnetic effects. Here, we explore the relationships between rock-magnetic parameters retrieved using relatively rapid and widely pre-conducted measurements and TS API results from late Cenozoic basaltic rocks. We selected rock-magnetic parameters quantified from strong-field high-temperature thermomagnetic curves, magnetic hysteresis loops, and back-field isothermal remanent magnetization demagnetizations. We provide new data pairs of rock-magnetic parameters and TS API results for 41 basaltic rock samples from 8 sites (cooling units) in Northeast China. Then, by compiling them with published data of similar quality, we compiled 133 pairs of rock-magnetic and TS API data at the sample level (38 sites). Using this data compilation, the following topics of interest were identified: Magnetic coercivity (Bc) and remanence coercivity (Bcr) among the hysteresis parameters, and the thermomagnetic parameter ITC|m| (an index of thermal change quantifying an average of the differences in saturation magnetization at a full temperature range of during a single heating–cooling run) allow meaningful and efficient discrimination between data subsets divided by “success” or “failure” in the API results. We propose sample preselection criteria for the TS experiment: a minimal set of Bc ≥ 13 mT (or Bcr ≥ 26 mT) and ITC|m|≤ 0.15. Moreover, extended consideration based on the preselection criteria may allow the screening of potentially biased specimen/sample-level API estimates in the site-averaged determination of such a site with a large within-site API dispersion. Graphical Abstract